An evaluative framework for mutual and employee-owned businesses - Tischer, D; Yeoman, R; White, S; Nicholls, A; Michie, J (Taylor and Francis, 2016)
Mutual and employee-owned businesses (MEOBs) continue to experience a revival in the UK, be it through the growth of building societies and financial mutuals, or the success of employee-owned businesses. In addition, government has promoted MEOBs by transferring public services into new corporate forms, citing reports of resilience and long-term success of MEOBs.